O desenvolvimento profissional de pedagogos da Educação Profissional e Tecnológica do Instituto Federal do Acre: contribuições de uma proposta formativa em ação - Pinheiro, Luciene de Almeida Barros (2018)
This research addresses questions related to the analysis of the research line: Teacher training processes for the technological teaching of the Federal Institute of Education, Science and Technology of Amazonas and had as objective to analyze in which aspects the participation in a process of elaboration of a proposal for the Continuing education for teachers of Vocational and Technological Education contributes to the professional development of pedagogues at the Rio Branco campus of the Federal Institute of Acre. The research was carried out in the period from August to September of 2017, in the evening shift. The fundamentals of the methodology were subsidized by Research-Action, consolidated from an Action Plan, consisting of four phases: diagnosis, elaboration, execution and evaluation. We used as instrument for data collection: application of diagnostic questionnaires and evaluative questionnaire; notes in the field diary and the realization of five formative meetings recorded through photographs and audio recordings, semistructured interviews with the five pedagogues, from the aforementioned campus. The research had a qualitative approach, which made possible the analysis of the collected material with a view to understanding the proposed object. To do so, we use Content Analysis as a method for organizing and interpreting the data. In this sense, he found that collective work and collaborative learning in the workplace itself is one of the factors that can contribute to the professional and personal development of the subject. These meetings served as a stimulating element of change, which helped professionals (researcher and research subjects) to rethink and re-signify their practices through study, research, collective and collective work, and critical and systematized, awakening in them the desire for change and the need for lifelong learning. Based on this training experience developed with the group and the results generated by the evaluative questionnaire, the product of the research was entitled "Continuing education of pedagogues to support teaching in Professional and Technological Education".